2013
DOI: 10.1016/j.crci.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

[bmim]BF4/[Cu(Im12)2]CuCl2 as a novel catalytic reaction medium for click cyclization

Abstract: Herein, a new application of an ionic liquid containing copper (I), ([Cu(Im 12 ) 2 ]CuCl 2 ), is introduced. This ionic liquid was used as an efficient catalyst for the click cyclization between organic azides and terminal alkynes in various solvents. Then, the mixture of [bmim]BF 4 /[Cu(Im 12 ) 2 ]CuCl 2 was used as a green catalytic medium for the multicomponent click synthesis of 1,4-disubstituted-1H-1,2,3-triazoles from a-halo ketones. The reactions were performed efficiently in this mixture and excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This catalytic system could be recycled five times without loss of its catalytic activity. 134 With great motivation through light-induced reactions such as photosynthesis, chemists have applied the light-induced click reaction 135 with varying exposure time, wavelength, and intensity to control the click reactions spatially and temporally. 136,137 Tasdelen et al reported the click reaction between benzylazide and simple alkynes in the presence of light as the activating agent (under irradiation at 350 nm) in the absence of a reducing agent.…”
Section: Combination Of Click Chemistry With Other Techniquesmentioning
confidence: 99%
“…This catalytic system could be recycled five times without loss of its catalytic activity. 134 With great motivation through light-induced reactions such as photosynthesis, chemists have applied the light-induced click reaction 135 with varying exposure time, wavelength, and intensity to control the click reactions spatially and temporally. 136,137 Tasdelen et al reported the click reaction between benzylazide and simple alkynes in the presence of light as the activating agent (under irradiation at 350 nm) in the absence of a reducing agent.…”
Section: Combination Of Click Chemistry With Other Techniquesmentioning
confidence: 99%
“…As far as we know, there is no report on the use of 1,2,3-triazole rings as a cationic source of chemically non-inert, especially SO 3 H-functionalized 1,2,3-triazolium ionic hybrids. Consequently, in continuation to our previous research works on the synthesis of new 1,4-disubstituted-triazoles by click methodology [25][26][27],…”
Section: Introductionmentioning
confidence: 57%
“…In order to introduce novel organic-inorganic Brønsted acidic ionic solid (BAIS) catalysts for the preparation of spirooxindole derivatives, 1-benzyl-4-phenyl-1H-1,2,3-triazole and 1-benzyl-1H-1,2,3-triazole substrates were prepared at the first step according to the previous literature with some extra modifications (Scheme 1) [25][26][27]32]. Multicomponent click reaction of benzyl chloride, phenyl acetylene, and sodium azide in the presence of a catalytic amount of CuI in a mixture of PEG 400 -H 2 O at room temperature after 25 min furnished 1-benzyl-4-phenyl-1H-1,2,3-triazole in 92% yield (Scheme 1a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the occurrence of difficulties in the purification phase for stripping the reaction wastes has caused their use as the reaction media not to be satisfactory in all aspects. [ 3–7 ] Therefore, non‐solvent applications of ILs emerging in the statue of “task‐specific ILs” are of particular importance. [ 8–11 ] Among them, Brønsted acidic ionic liquids (BAILs) due to numerous abundant advantages such as high thermal stability, high acidity, and simultaneously negligible release of hazardous gases, easy separation, and the ability to recycle and reuse for several times render the most important subset of task‐specific ILs.…”
Section: Introductionmentioning
confidence: 99%